Recent Trends and Advances in Wireless and IoT-enabled Networks - Jan, Mian Ahmad; Khan, Fazlullah; Alam, Muhammad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book covers a variety of topics in Information and Communications Technology (ICT) and their impact on innovation and business. The authors discuss various innovations, business and industrial motivations, and impact on humans and the interplay between those factors in terms of finance, demand, and competition. Topics discussed include the convergence of Machine to Machine (M2M), Internet of Things (IoT), Social, and Big Data. They also discuss AI and its integration into technologies from machine learning, predictive analytics, security software, to intelligent agents, and many more. Contributions come from academics and professionals around the world. Covers the most recent practices in ICT related topics pertaining to technological growth, innovation, and business; Presents a survey on the most recent technological areas revolutionizing how humans communicate and interact; Features four sections: IoT, Wireless Ad Hoc & Sensor Networks, Fog Computing, and Big Data Analytics.
Chapter1: A Distributed Trust Management Model for the Internet of Things (DTM-IoT) -- Chapter2: A Review of Current Security Issues in Internet of Things -- Chapter3: A Review of Internet of Things (IoT) Connectivity Techniques -- Chapter4: An Evolutionary Game-Based Mechanism for Unwanted Traffic Control -- Chapter5: Usability Attributes for Mobile Applications: A Systematic Review -- Chapter6: A Review on Integration of Scientific Experimental Data through Metadata -- Chapter7: Passive RFID Localization Systems in Internet of Things -- Chapter8: Internet Traffic Flow Analysis in Fog Computing: An Experimental Case Study -- Chapter9: Seven Pillars to Achieve Energy Efficiency in High Performance Computing and Big Data: An Application Perspective of Fog Computing -- Chapter10: Scheduling Algorithms for High performance Computing: An Application Perspective of Fog Computing -- Chapter11: A Novel Energy Aware Design for Clustered Wireless Sensor Networks -- Chapter12: Internet of Things based Smart City Environment using Big Data Analytics-A Survey -- Chapter13: Enhancing Integrity technique using Distributed Query Operation -- Chapter14: EH-ARCUN: Energy Harvesting Approach towards Reliability with Cooperation in UWSNs -- Chapter15: Congestion aware and adaptive routing protocol for MANETs - A Survey -- Chapter16: Scalability analysis of DBR and EEDBR in terms of delay, throughput and path loss in UASNs -- Chapter17: A Parametric Performance Evaluation of Batteries in Wireless Sensor Network -- Chapter18: Machine Imagination: A Step towards the Construction of Artistic World through Storytelling -- Chapter19: Geo-spatial division based geographic Routing for Interference avoidance in UWSN's -- Chapter20: DEAR-2 An Energy-aware Routing Protocol with guaranteed Delivery in Wireless Ad-hoc Networks -- Chapter21: Master Key Based Light Weight Key Negotiation Scheme for WSNs -- Chapter22: Distributed Monitoring Architecture for Industrial Safety Based on Gear Fault Diagnosis -- Chapter23:Nodes density analysis for WBAN schemes in terms of Stability and Throughput -- Chapter24: Internet of Things (IoTs) Research Challenges -- Chapter25: Managing and Processing Information in the Internet of Things based Smart City Environment using Big Data Analytics -- Chapter26: Adaptive Transmission based Geographic and Enhanced Opportunistic Routing for UWSN -- Chapter27: Exploring "IoT" Applications for Disaster Management: Identifying key factors and proposing future directions -- Chapter28: Spam User Detection through Deceptive Images in Big Data -- Chapter29: A Tool for Knowledge-oriented Physics-based Motion Planning and Simulation.
Keywords: Telecommunication; Computational intelligence; Artificial intelligence; Technological innovations; Communications Engineering, Networks; Computational Intelligence; Artificial Intelligence; Innovation and Technology Management